Relationships between conceptions of learning approaches to study and students' judgements about the value of their experiences of networked learning - Peter Goodyear; Mireia Asensio; Chris Jones; Christine Steeples; Vivien Hodgson (Association for Learning Technology, 2003)
This paper reports on an enquiry into relationships between students' views of their experiences of participating in networked learning courses and data on their conceptions of learning and approaches to study. It has been suggested in the literature on networked learning that students with more sophisticated conceptions of learning and students who take a deep approach to learning are more likely to benefit from, and have positive experiences of, networked learning. Drawing on a sample of almost 180 undergraduate social science students on four networked learning courses, we established that there were no strong links between students' judgements about their experience of networked learning and either their conceptions of learning or their approach to study. Further research is needed, but a practical implication of this study is that it is reasonable to expect all students to have positive experiences on well-designed and well-managed networked learning courses - not just those students with more sophisticated conceptions of learning or deep approaches to study.